Where are we Walking? An Introduction to a JPOSNA Year-Long Series on Gait Analysis in Pediatric Orthopedics: Invited Perspective - Shrader, Wade (Journal of the Pediatric Orthopaedic Society of North America, 2020)
Management of the ambulatory patient with cerebral palsy is complicated as each child has differences in the degree and extent of motor involvement; neurologic features (dystonia, ataxia) as well as other physical and social co-morbidities. No where else in pediatric orthopaedics is the care of these children/adolescents equally dependent on assessment tools and methods, treatment strategies, experience and the need for excellent support from our partners in rehabilitation medicine, occupational and physical therapy and orthotics. In this edition we begin a year-long study in this topic.